Isolation and Characterization of Full-Term Ammoniotic Fluid-derived Stem Cells - Ferdaos, Nurfarhana (2010)
Stem cell research has gained many attentions for their hope to cure myriad of disease ranging from genetically linked disorders to neurodegenerative diseases as well as injuries. Pluripotent stem cells signify the perpetual source of versatile cells, making them an excellent source for cell therapy. Current discoveries have reported amniotic fluid as an alternative source for pluripotent stem cells, termed amniotic fluid as an alternative source for pluripotent stem cells, termed amniotic fluid-derived stem (AFS) cells. AFS cells have been shown to express embryonic and adult stem cell markers while hindering the ethical controversies, which has been the biggest issue involving the well-known pluripotent stem cells; the embryonic stem (ES) cells. In addition, AFS cells also do not form tumors upon transplantation. To date, only amniotic fluid of mid-term pregnancies has been reported to yield AFS cells. However, the collection of mid-term AF samples involves invasive procedure (amniocentesis) that may result in several complications including abortion. Therefore, in study, we aim to isolate and characterize AFS cells from human and rat full-term pregnancies. The heterogeneity of amniotic fluid (AF) cells was observed upon culturing the cells under the optimized conditions, prior to isolation of stem cells by immunoselection against c-Kit, a marker for stem cell factor. The isolation of cells positive for c-Kit using Magnetic-Activated Cell Sorting (MACS) technology has resulted in enrichment of the c-Kit positive cells. Characterization of the c-Kit positive cells has demonstrated the expression of Oct-4, a marker for pluripotent cells and the formation of embryoid bodies (EBs), suggesting the possibility of AFS cells being present during full-term pregnancy in mammals including human. Hence giving hopes that full-term AFS cells would be the future alternative source for stem cell therapy.